Autoimmune Disease–Associated Haplotypes of BLK Exhibit Lowered Thresholds for B Cell Activation and Expansion of Ig Class‐Switched B Cells. Issue 11 (November 2015) - Simpfendorfer, Kim R.; Armstead, Brandon E.; Shih, Andrew; Li, Wentian; Curran, Mark; Manjarrez‐Orduño, Nataly; Lee, Annette T.; Diamond, Betty; Gregersen, Peter K.
Abstract : Objective: B lymphoid kinase ( BLK ) is associated with rheumatoid arthritis (RA) and several other B cell–associated autoimmune disorders. BLK risk variants are consistently associated with reduced BLK expression, but the mechanisms by which reduced expression alters human B cell function to confer autoimmune disease susceptibility are unknown. This study was undertaken to characterize the BLK risk haplotype and to determine associated B cell functional phenotypes involved in autoimmunity. Methods: The BLK risk haplotype association with RA (determined using whole‐genome sequencing data) was confirmed in 2, 526 RA cases and 2, 134 controls. Peripheral blood mononuclear cells (PBMCs) from RA patients, healthy adults, and umbilical cord blood were used to study B cell functional phenotypes associated with the BLK risk genotype. Association of the BLK haplotype with B cell phenotypes was analyzed using cell culture and flow cytometry. Results: Two insertion/deletions were found on the RA risk haplotype in BLK, and the reduction in BLK expression associated with the risk haplotype was confirmed in primary B lymphocytes. Carriers of the RA‐associated haplotype had evidence of lower basal B cell receptor (BCR) signaling activity, yet their B cells were hyperactivatable, with enhanced up‐regulation of CD86 after BCR crosslinking and greater T cell stimulatory capacity. The number of isotype‐switched memory B cells was also significantly increased in subjects carrying the risk haplotype. Conclusion: A major mechanism underlying the BLK association with autoimmune disease involves lowered thresholds for BCR signaling, enhanced B cell–T cell interactions, and altered patterns of isotype switching.